Bone marrow mesenchymal stem cells from leukemia patients inhibit growth and apoptosis in serum-deprived K562 cells - Wei, Zhaohui (BioMed Central, 2009)
BACKGROUND: The regulation of growth and apoptosis in K562 cells by human bone marrow mesenchymal stem cells (MSCs) from leukemia patients was investigated. METHODS: K562 cells were cocultured with leukemic MSCs under serum deprivation. Cell Counting Kit-8 (CCK-8), PI staining, Annexin V/PI binding and FACS assays were used to investigate cell proliferation, cell cycle status, and apoptosis of K562 cells cultures in the presence or absence of 10% serum. Western blotting was used to determine the levels of Akt, phosphorylated Akt (p-Akt), the BCL-2 family member Bad, and phosphorylated Bad (p-Bad) proteins in K562 cells after coculturing with MSCs. The effects of LY294002 (a specific inhibitor of PI3K) on protein expression were also determined. RESULTS: K562 cell proliferation was inhibited by coculture with MSCs and the dominant cell cycle was the G(0)-G(1 )phase. The proportion of apoptotic K562 cells was decreased and the levels of p-Akt and p-Bad were upregulated after exposing K562 cells to MSCs. However, when LY294002 was used, p-Akt and p-Bad proteins inK562 cells showed a significant reduction, while no distinct variation was seen in the nonphosphorylated Akt and Bad protein levels. CONCLUSION: Leukemic MSCs can inhibit K562 cell expansion and modulate the cell cycle to a state of relative quiescence. This allows the K562 cells to endure adverse conditions such as serum starvation. The PI3K-Akt-Bad signaling pathway may be involved in this antiapoptotic process via phosphorylation of the Akt and Bad proteins. Blocking MSC-induced transduction of the PI3K-Akt-Bad pathway may be a potential strategy for a targeted therapy to combat leukemia.